The Continuity of Sacred Urban Open Space: Facilitating the Indian Conversion to Catholicism in Mesoamerica. - Wagner, E. Logan (Religion & the Arts, 2014)
During the sixteenth century, the Spanish crown sent Mendicant friars of the Franciscan, Dominican, and Augustinian monastic orders to evangelize and convert the indigenous people of America. With huge populations to convert, spread over an extremely vast territory, a limited number of friars had to find expedient ways to facilitate the conversion effort. Among the many conversion strategies used by the Mendicant friars under the early guidance of Fray Pedro de Gante were: to locate places of Christian worship over or near native ceremonial centers and continue the use of ceremonial open urban space; the incorporation of native religious rituals deemed compatible with Catholic liturgy such as processions, music, art, and dance; the creation of new architectural forms and open urban spaces to provide a setting for these rituals; and the substitution of native rituals for Catholic ceremonies including adjusting native and Catholic ritual calendric dates. Based on recent architectural field surveys and ethnographic documentation, this research focuses on the architectural and urban space adaptations that the missionary friars undertook to facilitate conversion efforts.